2016
DOI: 10.1049/iet-nbt.2015.0120
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun cellulose acetate membrane for size separating and antibacterial screening of crude polysaccharides

Abstract: This study aims to produce electrospun cellulose acetate (CA) membrane as the alternative supporting medium for a separation of crude polysaccharides by electrophoresis and a screening of their antibacterial activity. Among the tested conditions of fabrication, electrospun CA membrane at 57% porosity showed the best separation of each polysaccharide from the standard mixture and the crude extract of via electrophoresis. As compared with the commercial CA membrane, the produced electrospun CA membrane demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…The average electrospun nano bers diameters were of 300.94 ± 57.19 nm, 318.56 ± 80.96 nm, 335 ± 58.24, and nm for CA17, CA18, CA19 and CA20, respectively. The ndings are in agreement with the study conducted by Chumpol and Siri (2016), in which the electrospun CA nano ber produced were in the diameter range of 367.6 − 458.0 nm. Previous research has revealed that ber diameter increases with increase polymer concentration (Ryu et al 2003;Kong and Ziegler, 2014).…”
Section: Fiber Distributionsupporting
confidence: 92%
“…The average electrospun nano bers diameters were of 300.94 ± 57.19 nm, 318.56 ± 80.96 nm, 335 ± 58.24, and nm for CA17, CA18, CA19 and CA20, respectively. The ndings are in agreement with the study conducted by Chumpol and Siri (2016), in which the electrospun CA nano ber produced were in the diameter range of 367.6 − 458.0 nm. Previous research has revealed that ber diameter increases with increase polymer concentration (Ryu et al 2003;Kong and Ziegler, 2014).…”
Section: Fiber Distributionsupporting
confidence: 92%
“…Moreover, electrospun cellulose acetate membrane was used as an alternative carrier for separation of crude extracts by electrophoresis. By controlling the porosity and pore size of membrane, it was used as a simple technical advantage for separation of high molecular weight and near molecular weight polysaccharides [43].…”
Section: Extraction Separation and Purification Of Acemannanmentioning
confidence: 99%